The validity of the Language Environment Analysis system in two neonatal intensive care units - Ståhlberg-Forsén Eva; Aija Anette; Kaasik Birgit; Latva Reija; Ahlqvist-Björkroth Sari; Toome Liis; Lehtonen Liisa; Stolt Suvi (WILEY, 2022)
Aim
To evaluate the validity of the Language Environment Analysis (LENA) system's automatic measures in two neonatal intensive care units supporting parent-infant closeness, and in two Finno-Ugric languages: Finnish and Estonian.
Methods
The sound environment of 70 very preterm infants was recorded for 16 h in the neonatal intensive care units with the LENA system roughly at the gestational age of 32 (+2) weeks. Of these, the recordings of 14 infants (20%, two 5-min samples with a high percentage of speech, totally 140 min) were analysed in detail and in two different ways. Parental closeness diaries were used to document the presence of the parents. Agreements between LENA system and human coder estimates were analysed.
Results
Findings showed a high variation in agreements. The highest agreements were found in female and adult word counts (r = 0.91 and 0.95). The agreements for child vocalisation count, conversational turns and silence were modest or low (r = -0.03 to 0.64).
Conclusion
Our study provides novel information on the validity of the LENA system in the neonatal intensive care unit. Findings show that the LENA system provides valid information on adult words, but LENA estimates for child vocalisations were less valid at this early age.